Implementing “Shopping Role Play” to Increase Speaking Ability - Ria Kamilah Agustina (Peneliti.net, 2022)
This study aimed to explore the role-play technique to improve the speaking skill of Accountancy Study Program students in ESP (English for Special Purpose) class implementing, especially in shopping Role Play. This study used descriptive qualitative research design with pretest and posttest. The subjects of this research were 12 students of Accountancy Study Program on Economy Faculty, Hasyim Asy’ari University. The pre-test was given before the treatment and post-test was applied after the treatment. After the test, the students are given the questionnaire to measure how satisfy they were in the previous activity. The data procedure consisted of preparing the dialog for the students (both as seller and buyer), providing activities that enabled the students to enrich their vocabulary by encouraging the students to open the dictionary, using various medias during the teaching and learning, giving more explanation about the use of modal verbs, providing activities to improve the students’ pronunciation, and implementing pair work to make them have more opportunity to practice to speak. The results of the research showed that the implementation of the shopping role play to improve students’ speaking skill was effective. They could perform more confidently. Moreover, their motivation and enthusiasm in English learning also improved. Furthermore, by employing the shopping role play, the students could freely express their feelings and make them able to explore their creativity in more ways to enable them facing the real life.